Fibromyalgia and Obesity: The Association Between Body Mass Index and Disability, Depression, History of Abuse, Medications, and Comorbidities. Issue 6 (September 2015) - Gota, Carmen E.; Kaouk, Sahar; Wilke, William S.
Abstract : Aim: The aim of this study was to determine the frequency of increasing body mass index (BMI) in fibromyalgia (FM) and to understand the impact of increasing BMI on FM. Methods: Patients with FM were divided into 3 BMI classifications: normal weight, overweight, and obese. We then sought relationships of increasing BMI to core process FM variables and symptoms and disability, as well as medical comorbidities and demographic, socioeconomic, psychiatric, and treatment data. Results: Of 224 patients, 0.4% were underweight; 25.9%, normal weight; 29.9%, overweight; 43.8%, obese. We found no differences within groups with regard to age, gender, demographics, FM symptoms, FM impact questionnaire scores, and meeting the American College of Rheumatology 1990 criteria and FM survey criteria. Patients with FM who are obese, compared with normal-weight patients, have higher depression scores measured by Patient Health Questionnaire 9 (13.2 [6.6] vs 10.5 [6], P = 0.03), report increased disability by Health Assessment Questionnaire Disability Index scores (1.3 [0.6] vs 0.9 [0.6], P < 0.001), exercise less (8.4% vs 25.4%, P = 0.003), have more medical comorbidities (1.5 [1.3] vs 0.7 [0.9], P < 0.001), take more medications for FM (3.5 [2.2] vs 2.1 [1.8], P < 0.001), and report higher prevalence of abuse (48% vs 33.9%, P = 0.016) and sexual abuse (17.3% vs 6.8%, P = 0.01). Conclusions: Compared with normal-weight patients, obese FM patients are more disabled, report more medical comorbidities, exercise less, have a higher incidence of abuse, report increased depressive symptoms, and take more medications for FM. Bivariate analysis showed association of increasing BMI with the Health Assessment Questionnaire Disability Index (not FM impact questionnaire) and depression. We confirm that the prevalence of overweight and obesity is high in FM and believe that physicians treating FM should be aware of our bivariate linear correlations and discuss weight loss with their FM patients. Even if increasing BMI is not intrinsic to FM, it contributes to poor mood and functional outcome and should be a treatment goal.